A study on cervical cancer screening in asymptomatic women using Papanicolaou smear in a tertiary care hospital in an urban area of Mumbai, India - Shaki, Omna (J Family Med Prim Care, 2018)
INTRODUCTION: Cervical cancer is the most common cause of death among women in developing countries. Among the Indian women, cervical cancer is the most common genital tract cancer. Papanicolaou (Pap) smear test plays a vital role in the detection of cervical cancer even in its premalignant condition. The aim of this study to evaluate the role of Pap smear in detecting premalignant and malignant lesions as well as nonneoplastic lesions of the cervix and to determine the prevalence of various lesions. MATERIALS AND METHODS: We screened 1100 women in the age group of 21–65 years who attended our medical camp organized by the hospital in outdoor patient department. All women was willing to give consent for screening by Pap smear test were included. RESULTS: Of 1100 cases, majority of the cases were benign comprising negative for intraepithelial neoplasia (NILM) of about 581 (52.8%) cases, 203 (18.4%) inflammatory, atypical squamous cells of undetermined significance 45 (4%), low-grade squamous intraepithelial lesion (LSIL) in 75 (6.8%), and high-grade squamous intraepithelial lesion (HSIL) in 74 (6%) women. Overall sensitivity and specificity for the detection of LSIL were 75.8% and 94.6% and those for the detection of HSIL were 68.9% and 98.6%. CONCLUSIONS: Pap smear test is a very easy, noninvasive, useful, simple, safe, and very economical tool to detect preinvasive cervical epithelial lesions. It is evident and proven that every woman above the age of 30–35 years must be subjected to cervical screening and this must be continued even in the postmenopausal period.